Basic Exchange Rate Theories - Charles van Marrewijk (Tinbergen Institute, 2005)
This four-chapter overview of basic exchange rate theories discusses (i) the elasticity and absorption approach, (ii) the (long-run) implications of the monetary approach, (iii) the short-run effects of monetary and fiscal policy under various economic conditions, and (iv) the transition from short-run to long-run in a sticky-price model with rational expectations. We provide ample anecdotal, historical, and heuristic information on the goodness-of-fit of the various exchange rate models based on simple graphs, statistics, and tests. Details are provided in technical notes.
Keywords: E; F; G; 330; exchange rates; expectations; monetary approach; elasticity; absorption; overshooting; monetary policy; fiscal policy; Wechselkurstheorie